Upaya Guru Bahasa Jawa dalam Menerapkan Unggah-Ungguh Basa pada Mata Pelajaran Bahasa Jawa Kelas X Semester Gasal di SMA Negeri 3 Brebes - Ambarwati, Ambarwati -; Alfiah, Alfiah -; Zaidah, Nuning (Universitas PGRI Semarang, 2022)
The background of this research is that there are still many teachers who have not used good efforts or methods in applying upload-ungguh basa to students. The formulation of the problem that can be taken is how the Javanese language teacher's efforts in implementing upload-ungguh basa in class X odd semester Javanese language subjects at SMA Negeri 3 Brebes and the obstacles encountered by the Javanese language teacher in applying upload-ungguh basa to students. The purpose of this study is to describe the form of the Javanese language teacher's efforts in applying upload-ungguh basa in class X odd semester Javanese language subjects at SMA Negeri 3 Brebes and to describe the obstacles encountered by the Javanese language teacher in applying upload-ungguh basa to students. This research is a descriptive type of research, with a qualitative approach. Sources of research data are Javanese language teachers and odd semester X grade students of SMA Negeri 3 Brebes with research data in the form of descriptions of observations, interviews and documentation conducted with Javanese language teachers and odd semester X grade students of SMA Negeri 3 Brebes. The data analysis technique uses data reduction, data presentation and conclusions. After analyzing the data, several research results were found as follows: the efforts made by Javanese language teachers in applying upload-ungguh basa to students include, 1) providing and conveying knowledge about upload-ungguh basa; 2) familiarize students with using the appropriate Javanese language when communicating; 3) conduct questions and answers to students using upload-ungguh base; 4) provide examples to students on how to behave well; 5) explain the learning material using the Javanese language. The obstacles encountered by the teacher when implementing the upload-ungguh base of students include: 1) the low awareness of students about the importance of learning the Javanese language; 2) many young people consider Javanese to be an ancient language; 3) students use Indonesian in everyday.